Periodization. Theory and methodology of training - Bompa, T. O.; Buzzichelli, C. A. (Human Kinetics, 2019)
Learn how to maximize training gains with Tudor O. Bompa, the pioneer of periodization training, and Carlo A. Buzzichelli, one of the world`s foremost experts on training methods, in the sixth edition of Periodization: Theory and Methodology of Training. Guided by the authors` expertise, the sixth edition offers information central to understanding the latest research and practices related to training theory while providing scientific support for the fundamental principles of periodization.